Investigation of the interaction of the construction of building S1 on underlying Thameslink. Issue 1 (2nd January 2021) - Foster, Jonathan; Paraskevopoulou, Chrysothemis; Miller, Richard
ABSTRACT: Building S1 is a 12-storey office development site that is situated within London, north of King's Cross Station. The site directly overlies twin Thameslink rail. The construction activities include: 3 m of surface excavation; insertion of piles either side of – and between – the tunnels; subsequent loading of the piles; and excavation of a 1-storey deep basement adjacent to the tunnels. The tunnels have live monitoring equipment installed around the lining. The aim of this project is to use the live monitoring data to produce a back-analysed finite element model that accurately predicts the tunnel displacement recorded. The latter is compared with the model of the stages of construction covered by the monitoring. The subsequent stages are modelled in order to have a holistic idea of the behaviour of the site. The model uses the assumptions involved with 2D plane strain, along with assuming homogenous and isotropic geotechnical units. Additionally, the London Clay is modelled with the hardening soil with small strain constitutive model (HSS). Sensitivity analyses show that the small strain parameters of HSS for the London Clay had the most significant effect on tunnel displacement compared with the strength, stiffness and permeability.